Relational capital and organisational resilience - Matos, F.; Tonial, G.; Monteiro, M.; Edvinsson, L. (Resilience in a digital age: Global challenges in organizations and society, 2022)
In the current context, marked by the challenges of the digital transformation, the climate emergency, the risks of the Covid-19 pandemic and the economic and health crisis, resilience emerged as a concept explaining how societies, systems, and subsystems can respond to shocks and better manage the inherent risks that are constantly changing. With the digital transformation and the increasing use of the internet by organisations, relational capital has emerged as one of the components of intellectual capital with greater relevance for the resilience and agility of organisations. Through the most recent literature review, this study explores the relationship between relational capital and firms’ resilience indicators. The results provide empirical evidence for the positive relationship between the two concepts and present the basis for developing an auditing framework of organisational resilience.